Seekers of the spiritual art and higher wisdom Encounters between art and esotericism - Kokkinen Nina; Illman Ruth (DONNER INST RESEARCH RELIGIOUS & CULTURAL HISTORY, 2022)
The current issue of Approaching Religion is based on a two-day seminar arranged in Helsinki in August 2020 by the Signe and Ane Gyllenberg Foundation under the title `Clear-sighted Art - Open Mind? Encounters between Art and Esotericism'. The seminar was arranged as a pendant to the art exhibition The Path to Hidden Knowledge that was open in the foundation's museum, Villa Gyllenberg, from June to October (see Camilla Granbacka's review in this issue). The organising committee of the seminar included Siiri Oinonen and Lotta Nylund from the Gyllenberg Foundation as well as Nina Kokkinen, who also curated the art exhibition, and Ruth Illman as academic representatives.